Effects of Salinity, Temperature, and Diet on the Biological Characteristics of Brachionus plicatilis Müller, 1786 - Quynh-Anh Tran-Nguyen; Truong Nhat Phan; Quang-Anh Tran; Hong Thi Mai; Thao Linh Phan Thi; Dang Doan Phan; Mau Trinh-Dang (Biology, 2025)
This study investigates the effects of salinity, temperature, and diet on the biological characteristics of the rotifer Brachionus plicatilis, an essential live feed in aquaculture. The results indicate that environmental factors have a significant influence on reproductive traits and survival. At a salinity of 5 ppt, B. plicatilis achieved the highest fecundity (25.50 ± 0.58 inds.), while the longest lifespan (273.00 ± 72.52 h) was observed at 35 ppt. The temperature had a strong influence on developmental rates, with the shortest juvenile period recorded at 35 °C (8.00 ± 0.00 h) and the longest lifespan at 20 °C (270.62 ± 30.38 h). The diet also played a critical role, with Chlorella vulgaris supporting maximum fecundity, whereas mixed diets prolonged lifespan to 290.50 ± 62.83 (h). These findings provide valuable insights into optimizing rotifer culture systems to improve aquaculture productivity and sustainability.